PEMANFAATAN CITRA SATELIT GOOGLE EARTH UNTUK PEMBUATAN PETA TATA GUNA LAHAN KECAMATAN KALIDONI - Sugema, Muarif; Rosyad, Farlin (Ensiklopedia Research and Community Service Review, 2025)
This study aims to analyze the effectiveness of Google Earth satellite imagery utilization in creating land use maps in Kalidoni District, Palembang. The research method uses a quantitative descriptive approach with remote sensing techniques and field surveys. Sampling was conducted at 150 points using stratified random sampling method. The results showed an interpretation accuracy level of 92.7% with a Kappa coefficient of 0.89. Land use distribution is dominated by settlements (35.2%), industrial areas (20.5%), and commercial services (15.3%). Temporal analysis for the 2019-2024 period shows residential area expansion of 12.5% and green open space reduction of 3.2%. This research proves that Google Earth imagery is effective for district-scale land use mapping with reliable accuracy levels.Keywords:  Land use, Google Earth, remote sensing, image interpretation,    Kalidoni Distric